Community Assistance in Facing the Covid-19 Pandemic through Education and Economic Programs - Masrifatin, Yuni; Putri, Lusi Dwi; Anwar, Khoirul; Makki, Mustaqim (STAI Miftahul ULa Nganjuk, 2023)
Community Assistance Activities in Dealing with the Covid 19 Pandemic Through the KPM-IK STAIM Nganjuk Program aims to help the community develop and pass the pandemic period by staying productive in the Education sector and the economy. The method in this research is Asset Based Community Developmet (ABCD) or asset-based community empowerment approach. Through the approach of Asset Based Community Development (ABCD) this can sustainably form the independence of the community in increasing income so as to improve its welfare. The results of the education sector research this activity has a positive impact with the change of students to better maintain the discipline of respecting teachers and science,while the economic sector of the community is helped in the manufacture of SIUP for MSMEs in pandantoyo village